Lowering whole cost for sugarcane‐based ethanol production by engineered Zymomonas mobilis. Issue 12 (5th October 2021) - Dai, Yonghua; Wu, Bo; Liu, Panting; Chen, Mao; Song, Chao; Gou, Qiyu; Liu, Renbin; Xu, Yansheng; Hu, Guoquan; He, Mingxiong
Abstract: Lowering cost will prompt the sustainable development of sugarcane‐based ethanol industry. In this work, we developed a low‐cost process for ethanol production from sugarcane by a genetically engineered Zymomonas mobilis . Fermentation media were first optimized, resulting in a 15.54% increase in ethanol fermentation efficiency as compared to control media. To further reduce the byproduct levan formation, a levansucrase‐encoding gene of Z. mobilis, sacB, was deleted through the type I‐F CRISPR‐Cas system, which resulted in a further elevation of both ethanol conversion ratio and productivity comparing with the starting strain ZMS912 (87.50% vs. 76.77%, 1.95 g/L/h vs. 1.71 g/L/h). Moreover, we conducted fed‐batch fermentation for ethanol production using sugarcane juice in 5 L bioreactors and employing the optimized media and engineered strain. The results showed that maximum ethanol titer of 81.59 g/L and productivity of 5.83 g/L/h were achieved. Finally, preliminary techno‐economic assessment demonstrated that our efforts to modify media and strain could reduce the processing cost of ethanol production from sugarcane juice, which provides the feasibility for economic ethanol production in the future. Abstract : Bioethanol is the primary force in future energy supply and carbon reduction. In this work, we developed a low‐cost process for ethanol production from sugarcane by a genetically engineered Zymomonas mobilis . The effective combination of two nitrogen sources can shorten the fermentation time and increase ethanol production. Gene mutation in Z. mobilis may further improve ethanol concentration and eliminated the formation of by‐products. Furthermore, higher ethanol titer and shorter fermentation time are achieved by fed‐batch fermentation in fermentor scale. The techno‐economic assessment demonstrated that this study provides the feasibility for the profitable production of sugarcane‐based ethanol.